Chronic Granulocytic Leukaemia: Effect of Elective Splenectomy on the Course of Disease. Issue 5951 (25th January 1975) - Spiers, A. S. D.; Baikie, A. G.; Galton, D. A. G.; Richards, H. G. H.; Wiltshaw, E.; Goldman, J. M.; Catovsky, D.; Spencer, J.; Peto, R.
Abstract : Conventional treatment by drugs or irradiation produces little prolongation of life in patients with chronic granulocytic leukaemia (C.G.L.) because the onset of metamorphosis of the disease from a chronic to an acute or subacute leukaemic process is not substantially postponed. Isolated clinical observations as well as both cytogenetic and cytokinetic evidence suggest that the spleen may play a special though not exclusive role in the development of undifferentiated cell clones which lead to metamorphosis of C.G.L. The results of a study of elective splenectomy during the chronic phase of the disease are reported. Twenty-six patients with C.G.L. underwent splenectomy during clinical remission of their disease, and there were no deaths after the operation. Twenty-one patients were alive at the time of writing, two of them eight years after splenectomy. Five cases of metamorphosis of C.G.L. to a refractory phase occurred whereas 10 would have been expected, a significant difference. After the onset of metamorphosis the quality of life was better in splenectomized than in non-splenectomized patients. These results show that splenectomy is a reasonable and safe procedure in C.G.L., and its apparently beneficial effects on prognosis justify a larger controlled clinical trial.